(untitled) (Web of Teachers: Inderscience Research, 2023)
This article considers the psychological aspects of individual well-being and its impact on the overall psychological state of a person. The article examines the key determinants of well-being, as well as the roles of self-esteem, social interactions, and psychological well-being. It is thought that the level of well-being of a person is closely related to his psychological health and quality of life. The discussion section includes a review of the importance of psychological support and strategies to promote well-being. The conclusion highlights the importance of understanding the psychological aspects of well-being and offers directions for future research and recommendations for practice.